LANGUAGE ACQUISITION SPEED IN A GAMIFIED LEARNING ENVIRONMENT - Xalilova Gulnoza Abdimannonovna (Modern American Journals, 2025)
This article analyzes the impact of a gamified educational environment on the speed of language acquisition. Based on modern pedagogical approaches and technologies, game elements are used to actively engage learners, enhance motivation, and accelerate the acquisition of language skills. The study examines the use of interactive applications, point-based systems, adaptive strategies, and competitive learning settings. The effectiveness of gamified environments is evaluated through a comparative statistical analysis of student performance versus traditional teaching methods.
Keywords: Gamification, language acquisition speed, educational technologies, interactive games, motivation, mobile applications, differentiated instruction, competition-based learning, game elements, pedagogical effectiveness.